STUDENTS ATTITUDES OF USING ONLINE GAME IN ENGLISH LEARNING AT THE ENGLISH LANGUAGE EDUCATION STUDY PROGRAM OF KHAIRUN UNIVERSITY - Faija Oya; Naniek Jusnita; Silvani Umar Ali (FKIP Universitas Khairun, 2022)
This study aims to find out the Students' Attitudes of Using Online Game in English Learning at English Language Education Study Program of Khairun University. The purpose of this study was to obtain information about students' attitudes in using online games for learning English. This is a qualitative methode design and use questionnaire and interview collect data. Involved 60 students of fifth semester. The researcher found that the students' attitudes using online games gave positive and negative results. The positive impact is that students use games to learn English because in play game they get learning English such as vocabulary and speaking English. The negative impact are that students who often use games are lowering health, Creating laziness, making players forget time, forgetting to study, forgetting tasks and responsibilities and excessive addiction. English learning through online game students has been identify to English learning in some activities, such as reading book, waching English video, and study in class.